Research on the supervision mechanism of new energy time-sharing rental vehicles in the background of carbon peak - Zhang, Wei; Liu, Hongli; Chen, Yejian; Wan, Xiaoyu (Science progress (1916), 2022)
At present, new energy time-sharing rental vehicles have become a new generation of travel modes, playing a positive role in environmental protection and being regarded as one of the most promising travel modes in the future. However, due to the rapid pace of market expansion, the problems in their development have come one after another, such as the leakage of personal information, difficulty refunding the deposit and other phenomena frequently occurring, causing problems for consumer user experience. The reasons are as follows: government policies and regulations need to be perfected; the level of enterprise operation needs to be observed, financing is difficult, and the level of consumer participation in supervision is low. Based on the traits of bounded rationality in the internet plus the periodic rental market, this paper introduces the government into the market subject and constructs a three-party dynamic evolution game model between the government, enterprises, and consumers to reveal the control strategy. This paper conducts a concrete analysis to verify the model using a case study by revealing the game process between the regulation strategy and behavior decisions of enterprises and consumers and provides a theoretical basis and reference for policy-making and decision-making. The results showed that when the key parameters are in different numerical ranges, the system has four evolutionary stability results. By appropriately increasing the number of subsidies and penalties, increasing the proportion of the compensation coefficient to consumers, and urging enterprises to reduce operating costs, government participation is conducive to the healthy development of the new energy time-sharing automobile industry.